Metal to ligand electron transfer for molecular activation and catalysis - Vidayaratne, Indu (University of Ottawa (Canada), 2010)
The ultimate goal of this thesis was to elucidate the metal oxidation state of the active species in the catalytic cycle for ethylene oligo- and polymerization, and understanding the nature of the catalyst/co-catalyst interaction. Central to achieving these goals is of course the judicious choice of the metal and ligand system enabling the isolation and characterization of species arising from the interaction catalyst precursor/activator, and an investigation of their catalytic behaviour. Two families of ligands (bis-iminopyridine) and pyrrolide anions have been used for different sets of reasons. The first is by excellence a non-innocent ligand commonly involved in the organometallic chemistry of the metal center, displaying an array of surprising transformations. We also discovered that this ligand is able to stabilize species where the metal deceivingly appears in low and unusual oxidation states, the spin density having being transferred to the ligand system instead. Remarkably however, this does not resolve into a quenching of the reactivity of the metal center whose behavior remained in fact as one could expect for genuine low-valent species. We have tried to elaborate further on this information. Chapter 2 is a study on the divalent chromium complexes of this particular ligand system and on its catalytic behavior. A divalent chromium complex of bis(imino)pyridine, {2,6-[2,6-(i-Pr) 2PhN=C(CH3)]2(C5H3N)}CrCl 2 (2.1), was prepared with the aim of studying its reactivity with alkylating agents. Despite the appearance of the metal center in a rare monovalent oxidation state, the square-planar geometry of the Cr atom suggests that the metal is most likely divalent, with the electron housed in the ligand pi* orbital. In Chapter 3 we have further elaborated on the concept of electron transfer and explored the direct reduction of the chromium complexes prepared in chapter two Reduction of {2,6-[2,6-(i-Pr) 2PhN=C(CH3)]2(C5H3N)}CrCl (2.3) with NaH afforded a rare case of dinitrogen fixation on chromium. The dinuclear dinitrogen complex {[{2,6-[2,6-(i-Pr) 2PhN=C(CH3)]2(C5H3N)}Cr(THF)] 2(mu-N2)}.THF (3.1) was isolated and characterized. In Chapter 4 we have extended the concept of reduced species of this ligand system with a brief exploration on vanadium. In spite of their very close structural similarity, the two species have completely different nature. The first is paramagnetic and may be regarded as generated by the two-electron attack of two formally zero-valent vanadium moieties on the same N2unit. In the nearly diamagnetic 4.3 instead, the N2 unit has been reduced by two vanadium atoms, formally divalent. Structural analysis and DFT calculations have indicated that partial reduction of the bridging nitrogen occurred for both complexes while, in the case of 4.1, substantial metal-to-ligand electron transfer also occurs. The second family of ligand systems examined in this thesis work was provided by pyrrolide-based organic molecules. The motif of electron storage has been further investigated by using a dianionic ligand bearing a central 1t-system which can be constrained by sterics at bonding distance to the metal center. The Cp-like features of pyrrolide anions and the fact that pyrrole/chromium provides a catalytic system for the commercial production of 1-hexene prompted this study reported in Chapter 5. In Chapter 6 we have introduced an electron storage device in the pyrrole based ligand system and report a study for their use in vanadium and titanium chemistry. The deprotonation of the tripyrrole MeTPH2 [MeTPH2)2,5-[(2pyrrolyl)(C6H5)2C] 2(MeN C4H2)], containing one N-methylated pyrrolyl ring, was carried out with 2 equiv of KH. In the anionic unit of the complex, the two identical {2,5-[(C4H3N)CPh2] 2[C4H2N(Me)]}Ti moieties are bridged by one nitride atom and one NH group. Isotopic labelling experiments as well as NMR spectroscopy and chemical degradation clearly indicated that the bridging nitrogen atoms were originated from nitrogen gas cleavage. The hydrogen atom on the imide residue was provided by the solvent most likely via a radical-type of attack of an intermediate reduced species. (Abstract shortened by UMI.)
Keywords: Chemistry, Molecular.